2021
DOI: 10.1073/pnas.2100338118
|View full text |Cite
|
Sign up to set email alerts
|

Modern Siberian dog ancestry was shaped by several thousand years of Eurasian-wide trade and human dispersal

Abstract: Dogs have been essential to life in the Siberian Arctic for over 9,500 y, and this tight link between people and dogs continues in Siberian communities. Although Arctic Siberian groups such as the Nenets received limited gene flow from neighboring groups, archaeological evidence suggests that metallurgy and new subsistence strategies emerged in Northwest Siberia around 2,000 y ago. It is unclear if the Siberian Arctic dog population was as continuous as the people of the region or if instead admixture occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Human intentionality likely drives some of these size changes, but a suite of unintentional actions and nonhuman factors is also surely at work. In Siberia, no Pleistocene canid remains are widely accepted as dogs, but dogs are well documented in Siberian forager contexts by the early Holocene (~9000 years ago) and are widespread in southern Siberian pastoralist and agriculturalist societies by the Late Holocene (~3000 years ago) ( 6 , 22 25 ). Examination of skeletal remains from 199 dogs from 28 Siberian archaeological sites shows a gradual decrease in body mass through the Holocene, with the overall mean being just 16.4 ± 4.64 kg (Table 1) ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human intentionality likely drives some of these size changes, but a suite of unintentional actions and nonhuman factors is also surely at work. In Siberia, no Pleistocene canid remains are widely accepted as dogs, but dogs are well documented in Siberian forager contexts by the early Holocene (~9000 years ago) and are widespread in southern Siberian pastoralist and agriculturalist societies by the Late Holocene (~3000 years ago) ( 6 , 22 25 ). Examination of skeletal remains from 199 dogs from 28 Siberian archaeological sites shows a gradual decrease in body mass through the Holocene, with the overall mean being just 16.4 ± 4.64 kg (Table 1) ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could have occurred through human-dog colonization of regions occupied by foragers, long-term uncontrolled dog dispersals to such regions, or even sustained trade in dogs between societies. A recent genomic study clearly identifies increasing European or Near East ancestry in Siberian dogs over the past 2000 years, including even in some arctic dogs in Northwest Siberia ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our histories of colonization and dispersal radically change domestication histories, regardless of their causes. With dogs, such processes have resulted in novel intermixing of dog populations in some areas and the near complete termination of others (Ameen et al, 2019; Bergström et al, 2020; Feuerborn et al, 2021). Humans and domestic animals are just two of many actants at work in the unfolding of domestication, and like all forms of evolution, these processes too involve various entanglements, not just one hand directing a species to a known outcome.…”
Section: Domestication Emplacedmentioning
confidence: 99%
“…However, these latter efforts are hampered by a lack of good theoretical predictions for continuous, two-dimensional models (Felsenstein, 1975;Barton, Depaulis and Etheridge, 2002), and simulations can provide a valuable tool in the absence of analytical theory. The dramatic increase in the number of published whole-genome sequences in the last 20 years (1000Genomes Project, 2010Mallick et al, 2016;Palkopoulou et al, 2018;Feuerborn et al, 2021), and the advent of ancient genomics (Green et al, 2010;Rasmussen et al, 2010), have revealed previously unknown migration events in the history of several species, such as dogs (Bergström et al, 2020), horses (Librado et al, 2021), elephantids (Meyer et al, 2017), and humans (Lazaridis et al, 2014;Fu et al, 2016). Since migration of populations involves spatial displacement, populations trace their ancestry to different geographic locations (Ralph and Coop, 2013;Osmond and Coop, 2021;Wohns et al, 2022).…”
Section: Introductionmentioning
confidence: 99%